2014
DOI: 10.1371/journal.pone.0098512
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of TLR2 N-Glycans: Critical Role in ArtinM Immunomodulatory Activity

Abstract: TLR2 plays a critical role in the protection against Paracoccidioides brasiliensis conferred by ArtinM administration. ArtinM, a D-mannose-binding lectin from Artocarpus heterophyllus, induces IL-12 production in macrophages and dendritic cells, which accounts for the T helper1 immunity that results from ArtinM administration. We examined the direct interaction of ArtinM with TLR2using HEK293A cells transfected with TLR2, alone or in combination with TLR1 or TLR6, together with accessory proteins. Stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 56 publications
(59 reference statements)
1
46
0
4
Order By: Relevance
“…Regarding the ArtinM-induced activation of macrophages, it is largely due to the recognition of TLR2 N-glycans [10,11], leading to the increased production of IL-12. This property, which was also demonstrated by y-ArtinM, induces Th1 immunity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the ArtinM-induced activation of macrophages, it is largely due to the recognition of TLR2 N-glycans [10,11], leading to the increased production of IL-12. This property, which was also demonstrated by y-ArtinM, induces Th1 immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that n-ArtinM induces the release of IL-12 and IL-10 by macrophages in a TLR2-dependent manner [11]. In this study, we investigated the ability of the y-ArtinM to induce IL-12 and IL-10 production in murine macrophages and evaluated whether the activity was TLR2-dependent.…”
Section: Y-artinm and N-artinm Induce Mast Cell Degranulationmentioning
confidence: 95%
See 2 more Smart Citations
“…A resposta mediada por TLR2 e induzida por ArtinM não apenas desencadeia a síntese de IL-12, mas também a produção da citocina anti-inflamatória IL-10 (PANUNTO- CASTELO et al, 2001;MARIANO et al, 2014).…”
Section: Discussionunclassified